Usability of three finger-stick whole blood HIV self-testing kits among men who have sex with men and female sex workers in Yaounde and Douala, Cameroon - Noah, JP Yves Awono; Ndié, Justin; Ndongo, Francis Ateba; Kana, Rogacien; Yongwa, Onesimus; Bonyohe, Martial; Mboussam, Plessy Hedgar; Avang, Tatiana Palisson; Moulioum, Fatima; Naah, Félicité Tabala; Tchikangni, Gutenberg; Nzaddi, Audrey Djomo; et al. (Archives of Clinical and Biomedical Research, 2025)
Background: The use of fingerstick HIV self-testing (HIVST) represents a novel approach to improving HIV screening, particularly among at-risk populations. However, there is currently a paucity of empirical evidence on its usability in Cameroon, necessitating the development of robust empirical evidence before this approach can be scaled up. Objective: This study assessed the usability of three HIVST kits among men who have sex with men (MSM) and female sex workers (FSWs) in Cameroon. Materials and Methods: An observational study was conducted in 14 community-based organisations (CBOs) in Yaoundé and Douala between the 11th and 22nd of June 2022. The study population consisted of FSWs and MSM aged 21 years and over who agreed to participate in the study. Once recruited, participants received counselling, unassisted finger-stick whole blood HIV self-testing and condoms. Data was collected using an administered questionnaire. Three finger-stick whole blood HIV self-testing kits were used in the study: Mylan, Sure Check and Check Now. The analysis was conducted using SPSS 27 software and the main outcomes were presented with a 95% confidence interval (95% CI). Results: Of the 815 participants who completed the HIV blood selftest, the median age was 27 years and 56.1% were FSWs. One in ten participants had never undergone an HIV test. The successful test performance for the Check Now, Sure Check and Mylan tests were 98.5%, 97.8% and 94.7%, respectively. In addition, the proportions of correct interpretation of results were 83.1%, 79.3% and 79.8%. The agreement between a participant's blood-based HIV self-test result and those of trained investigator-observers results was moderate with Check Now (κ=0.486; 95% CI: 0.366-0.605; p=0.001), whereas agreement with Sure Check (κ=0.36) and Mylan (κ=0.372) was low. Similarly, the proportions of good usability were 82.0%, 77.9% and 75.3 respectively. On multivariate analysis, participants who had difficulty drawing blood with the micropipette were more likely to fail the self-test (aOR=0.1; 95% CI: 0.0-0.3; P = 0.005). Conclusion: The use of fingerstick whole blood HIV self-testing kits by key populations in Cameroon is a viable method of HIV testing. However, issues have been identified with regard to interpretation, thereby underscoring the necessity for further training in order to enhance the accuracy of these tests and optimise the effectiveness of HIV prevention interventions.